Architectures and Spaces for Care: Recent Contributions to Spanish Postmodern Architectural Culture Led by Women Architects - Maria Isabel Alba Dorado (Feminismo/s)
Nowadays we observe how many of our cities and other inhabited spaces have been conceived by and for a subject that represents an androcentric model that focusses on the productive, with the result that aspects of architecture such as assistance and care have been underestimated. Faced with this neglect of issues that are considered by society as feminine, a series of feminist struggles have, over the course of decades, been demanding more equitable, inclusive spaces and cities that take into consideration tasks relating to care and reproduction in architectural practice. With regard to the Spanish architectural scene, since the end of the 20th century it has been possible to observe the emergence of a series of professional practices led by women architects that have used the concept of femininity as a creative argument in an effort to approach the profession from different perspectives and open up new areas of activity and debate within which they are free to develop their professional careers. These are based around a critique of modern architectural positions associated with an idealistic vision of society that takes as a reference a neutral gender far from all complexity and excludes the differences between people to establish a paradigm shift from and with feminisms. In this regard, this article aims to present a series of recent professional practices led by Spanish women architects during the period 1978-2008 who, from architecture and urban planning, as well as other peripheral positions such as the arts and social action, have worked around women’s experiences and lent prominence to day-to-day life and care. Its purpose is to determine some of the singular aspects of the contributions made by women to Spanish postmodern architectural culture. This study will allow us to observe how many of these contributions take shape in a series of actions, attitudes and ways of working that envisage the beginning of a shift in how the profession is practised; a shift that departs from the predominant canon to define new strategies and ways of approaching architectural practice that are more in line with the needs of women and non-normative subjects.